Measurement of Atmospheric Neutrino Cross-Sections on Oxygen, Water and Argon using Nuwro Event Generator - Iflah Rasool Shaik; Qudsia Gani; Mir Hameeda (Iranian Journal of Astronomy and Astrophysics)
Neutrinos were produced immediately after Big-bang. These are the most abundant particles after photons. Neutrinos are literally jam packing the Universe and are associated with some of the deepest mysteries of nature. These are excellent carriers of information from the past of Universe through sources like bursting stars and black holes which we do not have a direct access to. Consequently, there has been a surge in the study of neutrinos and their interaction with matter. However, since neutrinos are very weakly interacting particles, these have feeble cross-sections. Nonetheless, cross-section measurement is the basic ingredient for any higher order neutrino studies. Therefore, in this work we report the cross-section measurements of neutrino interactions with three atmospheric gases viz; Oxygen, Water and Argon. This study is done using NuWro event generator. Nuwro is a Polish code developed by some eminent researchers at Wroclaw University of Poland. It is configured using well known physical models of neutrino interaction. The cross-section measurements are taken in an energy interval of hundreds of MeV to a few GeV,which is also best suited to study neutrino oscillations. We also try a novel way to define the scattering potential for neutrino interactions as a function of initial neutrino flux.